The Development Path of the Lighting Industry in Mainland China: Execution of Energy Conservation and Management on Mercury Emission - Li, Zhongguo (Int J Environ Res Public Health, 2018)
The development path of the lighting industry in mainland China was studied in this work. Lighting electricity accounts for about 12% of social electricity consumption in mainland China, while only approximately 15% of electricity is conversed into light when incandescent light bulbs are used. To reduce electrical energy consumption and mercury emission from coal burning in the lighting industry, China worked out a roadmap to replace incandescent light bulbs with energy-saving fluorescent lamps (FLs). However, FL products utilize mercury to give out light and release mercury in their production, consumption and disposal processes. Therefore, the challenges of the lighting industry that mainland China are facing are controlling mercury pollution through the environmentally-friendly producing of fluorescent lamps, effective collecting and treating of spent fluorescent lamps. It was proposed that to effectively reduce energy consumption and mercury pollution, a good way to do this is developing energy-saving and mercury-free light emitting diode lighting industry. The mainland China Government’s strategies to develop lighting industry are worthy of consideration and emulation by other countries.